2018
DOI: 10.3758/s13420-018-0346-x
|View full text |Cite
|
Sign up to set email alerts
|

North American river otters (Lontra canadensis) discriminate between 2D objects varying in shape and color

Abstract: We investigated the ability of North American river otters (Lontra canadensis) to visually discriminate between 2D objects. The otters learned to discriminate between stimuli using multiple visual features and then were tested with stimuli in which one of the features was eliminated (color or shape). Two adult otters were trained in a two-alternative forced choice task to discriminate between a red circle and a blue triangle. Test sessions included probe trials containing novel shapes, colors, or shape-color c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(22 citation statements)
references
References 69 publications
1
20
1
Order By: Relevance
“…In this study, we found that harbor seals discriminate between objects using the visual features of shape rather than brightness, at least for the objects we used in the experiment. This result differs from those of previous studies involving other terrestrial species (Elmore et al 2009, Gosset and Roeder 2000, Lucon-Xiccato et al 2019, Minini and Jeffery 2006, DeLong et al 2019. For terrestrial species, color or brightness difference is a significantly important parameter for foraging and avoiding predators (Bacon and Bugrhardt 1976).…”
Section: Discussioncontrasting
confidence: 90%
“…In this study, we found that harbor seals discriminate between objects using the visual features of shape rather than brightness, at least for the objects we used in the experiment. This result differs from those of previous studies involving other terrestrial species (Elmore et al 2009, Gosset and Roeder 2000, Lucon-Xiccato et al 2019, Minini and Jeffery 2006, DeLong et al 2019. For terrestrial species, color or brightness difference is a significantly important parameter for foraging and avoiding predators (Bacon and Bugrhardt 1976).…”
Section: Discussioncontrasting
confidence: 90%
“…The otters were often motivated to participate in this cognitive task even when it could be quite challenging for the otters to learn a conceptual rule. For example, although one otter's performance was not significantly different than chance during the first test of the second experiment [20], the otter would still readily participate on every trial (performance on later tests was approximately 70% correct, with the other otter achieving approximately 80% correct in the first experiment). In addition to these cognitive tasks being enriching for the animal subject, it also allows researchers to learn more about the cognitive and perceptual abilities of many understudied species that are kept in zoos.…”
Section: Introductionmentioning
confidence: 97%
“…The animal must use their cognitive skills to engage in the task they are participating in, which could be classified as cognitive enrichment [3]. Two studies used a two-alternative forced-choice task to study the perceptual and cognitive abilities of North American river otters [20,21]. In this task, the otter is trained to choose between two different visual stimuli on each trial.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations